PENGARUH SERVICE EXCELLENCE TERHADAP CUSTOMER DELIGHT PADA PELANGGAN DOPAMINE CAFÉ RINGROAD - Purba, Saut; Sipahutar, Robinson; LG, Lambas Marisi Tua (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine the effect of service excellence on customer delight for Dopamine Café Ringroad customers. This type of research is descriptive quantitative. The population in this study was Dopamine Café Ringroad customers who visited from January to June 2024, totaling 10,800 people. The sample in this study was 99 respondents using the Sample Random Sampling technique. The data analysis methods used are Instrument Test, Classic Assumption Test, Simple Linear Regression Test, Hypothesis Test and Coefficient of Determination Test. The research results show that service excellence has a positive and significant effect on customer delight among Dopamine Café Ringroad customers